2011
DOI: 10.1007/s10669-011-9307-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal GSM RF and ELF EMF effects upon rat BBB permeability

Abstract: Since the late 1980s, our group has examined the effects of radiofrequency electromagnetic fields (RF-EMF), including pulse-modulated waves of the type emitted by mobile phones, upon the blood-brain barrier. In more than 2,000 rats, we have repeatedly demonstrated a passage of the rats' own albumin from the blood through the brain capillaries into the surrounding brain parenchyma at SAR values down to 0.1mW/kg. In most of these experiments, the animals were exposed in TEM-cells, ventilated by an external elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Histological changes in the permeability of the vascular endothelium were accompanied by an increase in the number of blood vessels in the thymic medulla, due to an increase in local blood flow and/or dilation of the vessels due to radiation. Similar results of increased permeability of the blood-brain barrier have been found after sub-thermal microwave exposure of rats [30]. These findings indicate that non-ionizing radiation caused a cellular protein response to acute stress (within 24 h) and an immediate and visible effect in the thymus morphology, Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Histological changes in the permeability of the vascular endothelium were accompanied by an increase in the number of blood vessels in the thymic medulla, due to an increase in local blood flow and/or dilation of the vessels due to radiation. Similar results of increased permeability of the blood-brain barrier have been found after sub-thermal microwave exposure of rats [30]. These findings indicate that non-ionizing radiation caused a cellular protein response to acute stress (within 24 h) and an immediate and visible effect in the thymus morphology, Fig.…”
Section: Discussionsupporting
confidence: 84%
“…studied the effect of EMF on BBB permeability in rats. It was found that the EMF exposure reduced memory functions 26 .…”
Section: The Blood Brain Barrier (Bbb) Damagementioning
confidence: 99%
“…Effects include increased cancer risk, cellular stress, increase in harmful free radicals, genetic damages, structural and functional changes of the reproductive system, learning and memory deficits, neurological disorders, and negative impacts on general well-being in humans. Damage goes well beyond the human race, as there is growing evidence of harmful effects (38) to both plants (39) and animals (40)'.…”
Section: Scientists and Doctors Warn Of Potential Severe Health Effecmentioning
confidence: 99%